Caliban’s Dialectic: Decolonizing Thoughts for the Black Question in Latin America - Dana Rosenzvit (Íconos)
On the existence of the Latin American culture, Roberto Fernández Retamar invites us to assume the negativity by which the European colonization has marked our continent by the proud re-appropriation of the term to speak about ourselves. This article is a decolonizing exercise to think from the margins of the political economies of production of cultural diversity developed in Latin America in relation to Afro-descendant populations (sub-alternized and racialized category by antonomasia). The location proposed is in the spatial epistemic fracture produced by the thinking of Frantz Fanon, seeking to create another postcolonial and decolonizing knowledge to address the tension between the presupposition of universality and the difference inherent to every nation-state in the current, unequal and combined world-system.